N-Gain To Test The Effectiveness Of Green Bean Juice And Soybean Juice To Increase Toddlers' Weight - Ramadhanintyas, Karina Nur; Utami, Yeni; Mulyati, Sesaria Betty (Jurnal Kesmas Prima Indonesia, 2025)
Statistics is one of the sciences that underlies the development of science, one of which is health science. Researchers are trying to implement green bean juice and soybean juice, the benchmark for the success of which is seen from the size of body weight before and after treatment. This study aims to measure the effectiveness of providing green bean juice and soybean juice interventions to toddlers using the N-Gain test. The method used in this study is quasi-experimental with a pretest-posttest design type. The number of samples is toddlers aged 1-2 years. Many as14respondents were divided into Group 1, green bean juice intervention, and Group 2, soy juice intervention. The data analysis technique used in this study was calculating the percentage of respondents' body weight multiplied by 100%, and then the N-Gain test was carried out. The study showed that 13 toddlers (92.8%) experienced an increase in body weight with low criteria, and as many as one toddler (7.2%) experienced an increase in body weight with moderate criteria. Green bean and soy juice with very ineffective criteria (16.4%) and less effective criteria can still increase toddlers' body weight (22.1%). The N-Gain test implemented the soy juice test more effectively than green bean juice given to toddlers to increase body weight.